Novel redox responsive chiral cyclometalated platinum(ii) complexes with pinene functionalized C^N^N ligands. (25th January 2016) - Zhang, Xiao-Peng; Liu, Fu-Qiang; Lai, Jian-Cheng; Li, Cheng-Hui; Li, Ai-Min; You, Xiao-Zeng
Abstract : A couple of unprecedented platinum(iv ) complexes have been facilely prepared, and distinct chiroptical performances are exhibited. Abstract : By oxidation of a couple of chiral cyclometalated platinum(ii ) complexes, Pt(La )(CC–Ph) (1a ) and Pt(Lb )(CC–Ph) (1b ) (La = (−)-4, 5-pinene-6′-phenyl-2, 2′-bipyridine and Lb = (+)-4, 5-pinene-6'-phenyl-2, 2'-bipyridine), a novel pair of platinum(iv ) enantiomers, Pt(La )(CC–Ph)3 (2a ) and Pt(Lb )(CC–Ph)3 (2b ), were obtained. According to the single crystal X-ray diffraction studies of2a and2b, the central platinum atom is wrapped by a C^N^N ligand and three phenylacetylene groups and exhibits a distorted octahedral geometry. Due to the different coordination configurations and electronic structures, complexes2a and2b are distinct from1a and1b not only in absorption and emission spectra, but also in their chiroptical properties. The oxidation reaction of1a and1b is a kinetically controllable process. Given different oxidants to complete the Pt(ii )-to-Pt(iv ) process, various oxidation rates were presented. The difference between the ECD spectra of complexes1a and2a has been confirmed through TD-DFT calculation and can be useful for designing new redox-responsive materials.